Analisis Tindakan Sosial Max Weber Dalam Rutinitas Pembacaan Qs. Al-Anbiya’:79 Di Pondok Pesantren Al-Fattah Kartasura - Izzul Haq, Ahmad (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study applies Max Weber's concept of social action to analyze the routine of reading the verse Al-Anbiya':79 at the Al-Fattah Kartasura Islamic Boarding School. Weber differentiated social action into four main types: traditional, rational-affective, value, and goal-rational action. Through this approach, this research aims to understand the motivation and meaning behind the activity of reading the verse Al-Anbiya':79 in the religious context of Islamic boarding schools. Islamic boarding schools as traditional Islamic educational institutions play an important role in maintaining religious practices passed down from generation to generation. Weber's analysis reveals that reading the verse AlAnbiya':79 can be understood as a traditional action carried out to maintain religious values and spirituality in the Islamic boarding school community. On the other hand, this action can also have a rational dimension towards the goal, such as getting blessings or obtaining blessings from God. The results of this study provide an overview of how religious values and traditions play a role in shaping daily life routines in Islamic boarding schools. The implication of this analysis is the importance of understanding how Islamic boarding schools as social institutions not only maintain traditions, but also adapt to modern values that are developing in contemporary society.